SCALAR DAMAGE BASED ON MICROPOLAR CONTINUA ”“ MESH-FREE APPROXIMATION - Gori, Lapo; Andrade, Marcella Passos; Silva, Ramon Pereira da; Penna, Samuel Silva; Pitangueira, Roque Luiz da Silva (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Recently, scalar damage models based on the micropolar continuum theory have been proposed, in order to represent the physically non-linear behaviour of quasi-brittle materials. Due to its regularization properties, widely investigated in elasto-plasticity, the micropolar theory represents a valid alternative for mitigating pathological phenomena that arise in the numerical simulations. In the last years, also the class of mesh-free methods have been shown to be capable to regularize the response of problems where localization occours. This paper investigates the coupling of micropolar damage models with mesh-free methods, with specific attention on the Element Free Galerkin (EFG) method. The micropolar theory is presented in a tensorial generalized form, and different scalar damage models are derived in a theoretical and computational unified framework for constitutive models. The computational aspects of the coupling between micropolar damage and mesh-free approach are also discussed, with specific attention on the implementation in the INSANE (INteractive Structural ANalysis Enviroment) system. Numerical simulations are presented in order to illustrate the proposed models.